Pengembangan e-LKPD Berbasis Project Based Learning untuk Meningkatkan Hasil Belajar Siswa pada Pembelajaran Fiqih - Agam Alfarizi, Aburizal; M.Nur, Azhar; Ninoersy, Tarmizi (Tadabbur: Jurnal Peradaban Islam, 2024)
The Purpose of this research is to enhance student learning outcomes on fiqh lesson by creating an electronic learning product namely a Developing electronic Students' Worksheet Based on Project Based Learning ( e-LKPD). Research and Development (R&D) utilizing the ADDIE Learning Statistics data analysis methodologies implemented in this research are the result of a product developed by reserchers and validated by material specialistis and media professionals. The sample that used by researeher was the class of VIII-3 which a mounted to 26 students. Validation result from media experts with an average score of 0,95 and material experts with an average score 0,97 indicate that credible project based e-LKPD in utilized in learning, according to research findings. Following the implementation of e-LKPD in learning, the percentage of students learning outcomes increased to 84,61% from 53,84% the educational result of students can be improved, which makes the application of e-LKPD in education an affective method.